Sustainable Housing Business Research Trend - Muhammad Ikhsan Setiawan; Singgih Tjatur Subagijo; Florianus Rooslan Edy Santosa; Kiki Nabila Kamilia; Haziman Wan Ibrahim (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: Good and coordinated administration is essential for completing a property. This study focuses on aligning individuals' control with their distinct objectives. Homebuilders strive to address problems as effectively as possible to attain the most significant success from multiple perspectives. Design/methodology/approach: SCOPUS.COM is a library of source-neutral abstracts and citations vetted by recognized experts in their respective disciplines. From 1985 to 2022, researchers discovered 835 documents on sustainable housing in the SCOPUS.COM database, according to (1) country or region, (2) source, (3) funding sponsor, (4) subject, and (5) affiliation. Findings: Indonesia ranks below Malaysia, India, and China in Asia and ASEAN but above Singapore and Thailand. Indonesia continues to be competitive in housing research and publication. Sustainability Switzerland has 54 documents, followed by the IOP Conference Series Earth and Environmental Science with 37, International Journal of Housing Science and Its Applications with 24, IOP Conference Series Material Science and Engineering with 19, Habitat International with 13, and Building and Environment with ten documents. Hong Kong, China, Korea, and Malaysia provide the most institutional funding, where the sources include DIKTI, ITS Surabaya, UNDIP Semarang, and U.I. Jakarta in Indonesia. Engineering has 386 documents, Social Science 334, Environmental Science 257, and Energy 161. The Netherlands, Malaysia, Hong Kong, and India account for most affiliations, while three documents from ITS Surabaya represent Indonesia. There are significant gaps in sustainable housing research and publishing. Supporting renewable energy is a global trend, and sustainable development must expand. Originality/value: This paper is original Paper type: Research paper